2014
DOI: 10.1186/1475-2840-13-32
|View full text |Cite
|
Sign up to set email alerts
|

The DPP-4 inhibitor sitagliptin attenuates the progress of atherosclerosis in apolipoprotein-E-knockout mice via AMPK- and MAPK-dependent mechanisms

Abstract: BackgroundThe dipeptidyl peptidase-4 inhibitor sitagliptin, a new anti-diabetic medicine, is effective in treating type 2 diabetes mellitus by increasing the activation and duration of action of glucagon-like peptide-1. Since atherosclerosis is the main pathological feature of diabetic cardiovascular complications, it is important to investigate the anti-atherosclerotic effect of sitagliptin and explore the relevant mechanisms.MethodsMale apolipoprotein-E-knockout mice were randomly divided into two groups and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 38 publications
5
76
0
1
Order By: Relevance
“…These inflammatory cytokines were reduced in the presence of sitagliptin, suggesting that sitagliptin has inhibitory effects on inflammation in response to proinflammatory agents such as LPS, which can lead to cardiovascular depression during sepsis. The present results are consistent with previous studies which have shown that sitagliptin can lead to reduced levels of proinflammatory markers, and may potentially contribute to the inhibition of cardiovascular complications (29,30).…”
Section: A B Csupporting
confidence: 83%
“…These inflammatory cytokines were reduced in the presence of sitagliptin, suggesting that sitagliptin has inhibitory effects on inflammation in response to proinflammatory agents such as LPS, which can lead to cardiovascular depression during sepsis. The present results are consistent with previous studies which have shown that sitagliptin can lead to reduced levels of proinflammatory markers, and may potentially contribute to the inhibition of cardiovascular complications (29,30).…”
Section: A B Csupporting
confidence: 83%
“…In addition, leukocyte cell-derived chemotaxin 2 (LECT2) can also play a role in atherosclerotic inflammatory reactions via JNK phosphorylation (Hwang et al, 2015). In addition, the DPP-4 inhibitor sitagliptin can reduce leukocyte-endothelial cell interactions and inflammation, and attenuate atherosclerosis progression via AMPK-and MAPK-dependent mechanisms (Zeng et al, 2014). Haeng Park et al (2014) also confirmed that the anti-atherosclerotic effects of Polygonum aviculare L. ethanol extract in ApoE -/-mice are mediated via the MAPK pathway.…”
Section: Discussionsupporting
confidence: 50%
“…Besides, DPP-4 inhibitors has been found to reduce hepatic expression of genes important for cholesterol synthesis (Flock et al, 2013). Sitagliptin reduced atherosclerosis progression in hyperlipidemic rabbits via its effect on lipid parameters and interfering with inflammatory and oxidative stress pathway (Zeng et al, 2014). However molecular and cellular mechanisms of how this drug lower lipid level (e.g.…”
Section: Discussionmentioning
confidence: 99%